Telomerase and its inhibitors in lung cancer: a literature review (Research, Society and Development, 2023)
Lung cancer is the second most common cancer in men and women in Brazil and the most common malignant tumor worldwide, being the leading cause of cancer-related death worldwide. The main reasons for the increased incidence rate are smoking and air pollution (Câncer de pulmão, n.d.). However, genetic factors also play an important role in lung cancer carcinogenesis, with telomerase being a key point in this process, along with its role in cellular senescence. In this sense, this study aims to evaluate how telomerase and its inhibitors are associated in the development of lung cancer. The present study consists of an integrative literature review on the performance of telomerase and its inhibitors in lung cancer, in which the PICO strategy (Acromium for Patient, Intervention, Comparison and Outcome) was used and the descriptors “telomeres” were crossed; "cancer"; “lung cancer” in Portuguese and English, in the following databases: Virtual Health Library (BVS); National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (SCIELO). From the final analysis of the full text of the 24 duly selected articles, it was possible to observe that lung cancer is directly related to the length of telomeres and the activity of the enzyme telomerase. It is therefore concluded that, in an attempt to find an effective treatment for cancer, new study targets on the telomerase enzyme are still needed, along with the follow-up of studies that are already in progress.